Case report: The MSI-L/p-MMR metastatic rectal cancer patient who failed systemic therapy responds to anti-PD-1 immunotherapy after stereotactic body radiation-therapy - Liu, Shijin; Zhang, Yiran; Lin, Yujian; Wang, Peize; Pan, Yunlong (Frontiers in Immunology, 2022)
Background Traditionally, patients with microsatellite stability (MSS)/microsatellite instability-Low (MSI-L)/proficient mismatch repair (p-MMR) metastatic colorectal cancer (mCRC) have had poor benefit from immunotherapy. Therefore, how to enhance the response of immunotherapy is still a challenge for MSS/MSI-L/p-MMR CRC patient. Case presentation We report a special case of a rectal cancer patient with programmed death-ligand 1 (PD-L1) negative expression, MSI-L/p-MMR, tumor mutational burden-low (TMB-L) and liver metastases, who partial response (PR) to immunotherapy after systemic therapy failure including chemotherapy, anti-angiogenesis therapy and stereotactic body radiation-therapy (SBRT). The computed tomography (CT) results showed that among three liver metastases had been reduction or disappearance after Tislelizumab treatment for three times. Besides, the carcinoembryonic antigen (CEA) and carbohydrate antigen 199 (CA199) decrease and maintained at a low level for 3 months. The progression-free survival (PFS) of patient has exceeded 3 months. Conclusions This case indicates that the patient with MSI-L/p-MMR mCRC can respond to anti-PD-1 immunotherapy after systemic therapy. And the SBRT (targeting liver metastases) may a method for increase-sensitivity of immunotherapy in CRC patients with MSI-L/p-MMR.